Naphthopyranone glycosides from Paepalanthus bromelioides - Vilegas, Wagner [UNESP]; Santos, Lourdes C. [UNESP]; Alecio, Alberto C. [UNESP]; Pizza, Cosimo; Piacente, Sonia; Pauw, Edwin De; Sano, Paulo T. (Elsevier, 1998)
Two new naphtho[2,3-C]pyran-1-one glycosides, paepalantine-9-O-β-D- glucopyranoside and paepalantine-9-O-β-D-allopyranosyl(1 → 6)glucopyranoside, were isolated from an ethanolic extract of capitula from Paepalanthus bromelioides and identified from their spectrometric data.
Keywords: Eriocaulaceae; Naphthopyranone glycosides; Paepalanthus bromelioides; glycoside; paepalatine 9 o beta dextro allopyranosyl (1-6) glucopyranoside; paepalatine 9 o beta dextro glucopyranoside; unclassified drug; antifungal activity; bactericidal activity; brazil; cytotoxicity; drug isolation; infection; plant